Migration to Next Generation IP Network (International Journal of Engineering and Computer Science, 2015)
This white paper will help service providers understand the benefits and economics associated withimplementing a Next Generation Network (NGN). Convergence is the process of interconnection oftraditional switched circuit networks (the PSTN and mobile networks) and packet-switched networks basedon the Internet Protocol (IP) for routing.